Effect of Brushing with Whitening Toothpaste on External Discoloration of Resin Modified Glass Ionomer Cement - Yosi Kusuma Eriwati; Rachel Puja Chrisanti; Ette Soraya Tadjuddin (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2025)
Introduction: Resin Modified Glass Ionomer Cement (RMGIC) is a restorative material that combines the properties of Glass Ionomer Cement (GIC) and Composite Resin. RMGIC is prone to external discoloration due to exposure of dark colored beverages such as coffee, tea, and Coca-Cola. Extrinsic stains of the overlaid material can be removed using whitening toothpaste. A lot of people drink Coca-Cola, however, there has not been many studies discussing the effect of whitening toothpaste brushing on the RMGIC discolored by Coca-Cola. Purpose: To analyze the effect of brushing with whitening toothpaste on RMGIC discolored by Coca-Cola. Methods: Thirty cylindrical RMGIC (GC Fuji II LC® Light-Cured, GC Corp, Japan) specimens, 6 mm in diameter, 2 mm in thickness were divided into 3 groups treated with 3 toothpastes respectively. The specimens were soaked in Coca-Cola for 7 days and then brushed using various toothpastes namely Pepsodent 8 Plus Whitening Toothpaste, Pepsodent Regular Toothpaste, and no toothpaste for 4 minutes 40 seconds. Results: Brushing with different toothpaste groups resulted in a significantly different increase in L* values (p<0.05), a significantly different decrease in b* and a* values (p<0.05). The color change caused by brushing Pepsodent 8 Plus Whitening Toothpaste was significantly different with brushing Pepsodent Regular Toothpaste. Conclusion: Brushing Coca-Cola discolored RMGIC with whitening toothpaste resulted in the greatest improvement in brightness and discoloration compared to other toothpastes.